Problems of magnetostratigraphy of Pleistocene loess-soil deposits of the South of Ukraine - V.G. Bakhmutov; D. V. Glavatskiy (Геофизический журнал, 2016)
Main principles of magnetostratigraphy, paleomagnetic method of measurement and its applying in Quaternary stratigraphy have been set forth. Results of Matuyama-Brunhes (M/B) boundary detection in loess-soil sediments of Ukraine and other territories given in the previous studies are presented. Attention has been paid to contradictions in determination of M/B boundary position and episodes of inverse polarity within Brunhes chron according to the data of different authors. The situation is notably shown on Roxolany section in West Black Sea region as an example. One of the reasons there can be increase of magnetometric equipment precision and quality of measurements which exclude the bias effects nowadays. Another reason is the contradictions in stratigraphic partition of sections that are located even within the same loess province. We have got informative data that allow to predetermine M/B boundary position in Roxolany section at 46.6 m depth between Lubny and Martonosha soil horizons which conforms to modern point of view of Ukrainian stratigraphers and corresponds to previous investigations of Dolynske section (M/B boundary was found at the level of Martonosha horizon). Further complex paleomagnetic studies of Pleistocene sections of Ukraine will help to revise and correlate still conflicting magnetostratigraphic charts.